SARS-CoV-2 in the environment: Modes of transmission, early detection and potential role of pollutions (2020)
The coronavirus disease 2019 (COVID-19) is spreading globally having a profound effect on lives of millions of people, causing worldwide economic disruption. Curbing the spread of COVID-19 and future pandemics may be accomplished through understanding the environmental context of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and adoption of effective detection tools and mitigation policies. This article aims to examine the latest investigations on SARS-CoV-2 plausible environmental transmission modes, employment of wastewater surveillance for early detection of COVID-19, and elucidating the role of solid waste, water, and atmospheric quality on viral infectivity. Transmission of SARS-CoV-2 via faecal-oral or bio-aerosols lacks robust evidence and remains debatable. However, improper disinfection and defected plumbing systems in indoor environments such as hospitals and high-rise towers may facilitate the transport of virus-laden droplets of wastewater causing infection. Clinical and epidemiological studies are needed to present robust evidence that SARS-CoV-2 is transmissible via aerosols, though quantification of virus-laden aerosols at low concentrations presents a challenge. Wastewater surveillance of SARS-CoV-2 can be an effective tool in early detection of outbreak and determination of COVID-19 prevalence within a population, complementing clinical testing and providing decision makers guidance on restricting or relaxing movement. While poor air quality increases susceptibility to diseases, evidence for air pollution impact on COVID-19 infectivity is not available as infections are dynamically changing worldwide. Solid waste generated by households with infected individuals during the lockdown period may facilitate the spread of COVID-19 via fomite transmission route but has received little attention from the scientific community. Water bodies receiving raw sewage may pose risk of infection but this has not been investigated to date. Overall, our understanding of the environmental perspective of SARS-CoV-2 is imperative to detecting outbreak and predicting pandemic severity, allowing us to be equipped with the right tools to curb any future pandemic.